(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objectives: to identify in the scientific literature the knowledge produced about skin tears injuries in the elderly. Methods: it is an integrative literature review (2014-2019), carried out by searching the databases/platforms National Library of Medicine, Biomedical Answers and Biblioteca Virtual em Saúde, with descriptors and the Boolean operators “and” and “or ”. Results: from the bibliographic search, selection and analysis, eight articles made up the sample. For skin tears injuries in the elderly, four pillars of care emerged: maintenance of organic and tissue homeostasis with a focus on proper nutrition and hydration; avoid trauma to senile skin, providing a safe environment with suitable devices; and the systematization of health care and education for elderly skin care. Conclusion: as prevention mechanisms, primary prevention is achieved through a unique care plan and health education activities, focused on risk factors and vulnerabilities, minimizing damage and complications.